2004
DOI: 10.2298/vsp0402125n
|View full text |Cite
|
Sign up to set email alerts
|

N-Methyl-3,4-methylenedioxyamphetamine-induced hepatotoxicity in rats: Oxidative stress after acute and chronic administration

Abstract: The increased index of lipid peroxidation and the decreased reduced glutathione levels suggested that MDMA application induced the state of oxidative stress in the liver. These changes were much more expressed after the single administration of MDMA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 24 publications
1
12
0
2
Order By: Relevance
“…Potential mechanisms include catecholaminergic stimulation or autooxidation of catecholamines (21), mitochondrial dysfunction and leukocyte recruitment and activation (6), and or coronary vasospasm-induced reperfusion ischemia (6, 21). Recent studies have shown that MDMA metabolites play an important role in the toxicity of this drug (12-15). For example, MDMA is metabolized to catechols, which subsequently form orthoquinones.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Potential mechanisms include catecholaminergic stimulation or autooxidation of catecholamines (21), mitochondrial dysfunction and leukocyte recruitment and activation (6), and or coronary vasospasm-induced reperfusion ischemia (6, 21). Recent studies have shown that MDMA metabolites play an important role in the toxicity of this drug (12-15). For example, MDMA is metabolized to catechols, which subsequently form orthoquinones.…”
Section: Discussionmentioning
confidence: 99%
“…Studies revealed that MDMA is metabolized to catechols that can undergo redox cycling, with the formation of reactive (and unstable) orthoquinones, generating large quantities of reactive oxygen and nitrogen species (11). The redox active metabolites of MDMA have also been implicated in the toxic effects of MDMA on the heart, kidney and liver (12-15) in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…A previous experimental study that investigated the effects of MDMA on the liver demonstrated that increased concentrations of superoxide dismutase, decreased levels of glutathione and increased lipid peroxidation were evident even after a single dose of MDMA [23]. Dose-dependent increases in lipid peroxidation were also observed.…”
Section: Discussionmentioning
confidence: 83%
“…In vivo studies in mice indicate that oxidative stress and high ambient temperature influence hepatotoxicity in mice (Carvalho et al 2004;Johnson et al 2002). MDMA given at higher doses and at high ambient temperature was associated with sings of oxidative stress and liver abnormalities (Carvalho et al 2002), and repeated injections of 10 mg/kg, but not 5 mg/kg, S-(+)-MDMA, produced some hepatic necrosis (Johnson et al 2002), with more pronounced effects in mice fed a vitamin E deficient diet than in mice receiving sufficient amounts of vitamin E. Studies in rats also found a dose dependent increase in signs of oxidative stress in the liver (Ninkovic et al 2004;Rusinyak et al 2004). …”
Section: Hepatotoxicitymentioning
confidence: 95%